Juan de Arguijo, Obra poética. Ed. de Sanko B. Vranich. Castalia. Madrid, 1971; 269 pp. (Clásicos Castalia, 40). - Aveleyra A., Teresa (El Colegio de México, 2007)
Se reseñó el libro: Obra poética. Ed. de Sanko B. Vranich.